Modernização periférica e desigualdade social: disputas no Pensamento Social Brasileiro - Marcos Abraão Ribeiro (Ciências Sociais Unisinos)
This paper examines in a comparative manner some interpretations of Brazil’s moderniza- tion and its relation to the issue of social inequality produced in Brazilian Social Thought. We seek to show the points of convergence and divergence between the perspectives of the group of interpreters analyzed here. On the basis of the comparative analysis of some of our main interpreters we look for resources that may contribute to a broad understanding of the phenomenon of social inequality, which is a central theme in Brazil today.